Multi-decadal variations of the South Indian Ocean subsurface temperature influenced by Pacific Decadal Oscillation. Issue 1 (1st January 2017) - Zhou, Xiaobing; Alves, Oscar; Marsland, Simon J.; Bi, Daohua; Hirst, Anthony C.
Abstract: Over recent decades, a strong subsurface cooling trend in the South Indian Ocean (SIO) occurred, despite a continuous sea surface warming. Previous studies suggest this long-term (around 1960–2000) cooling trend is mainly driven by remote Pacific atmospheric forcing or local Indian Ocean (IO) forcing. This study reveals that the dominant driver of the SIO subsurface cooling trend in different periods is closely related to the phase of Pacific Decadal Oscillation (PDO). Our results suggest that the local IO wind forcing is responsible for the majority of the subsurface cooling trend and overwhelms a weak warming trend induced by the remote tropical Pacific wind forcing during the negative-phase period of PDO during 1960–76. However, this situation reverses during the PDO positive-phase period during 1977–98. Our analysis suggests that the PDO strengthens/weakens the tropical Pacific trade winds during negative/positive phase periods. Furthermore, the multi-decadal variations in the western Pacific induced by PDO impact the SIO subsurface temperature via baroclinic Rossby waves.